14t+14t+t=

Simple and best practice solution for 14t+14t+t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14t+14t+t= equation:


Simplifying
14t + 14t + t = 0

Combine like terms: 14t + 14t = 28t
28t + t = 0

Combine like terms: 28t + t = 29t
29t = 0

Solving
29t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '29'.
t = 0

Simplifying
t = 0

See similar equations:

| (3/8)+(5/7)= | | -7x+12x-20=-9-6x | | 4y+10=-2(3y+1) | | 5x-(4x+6)=-4 | | 17st-16s+t= | | 18r+18r+9r-3r= | | 8x+4x+2+9=7x+3+4x | | 10t-4t-6+5t= | | (1/11)=x+(10/11) | | 6g+3(-8+2g)=1-g | | 4-9x=x+4 | | (-6m^2+9n^2-4n)-[(9m^2-4m+5n)+(-9m^2)+4n^2]= | | (2/5)=(1/4)+f | | 5g+3(-8+2g)=1-g | | 4m+3n=8 | | 3x-7x=44 | | x+5(x+6)+25-12(x-12+5)3x+2x-3y+56.25=25 | | (4/5)=(1/4)+f | | 6g+3(-6+4g)=1-g | | (14/4)y+(2/2)=3y-4 | | -4(x+1)-32=3x-7(x+6) | | -8-14+5b=11 | | -31-(4x)=-5-5(1+5x) | | (x/2)-6=(x/5)-3 | | x+(12/8)=(3/4)x | | x/15=3/5 | | x+(7/8)=2x-(7/8) | | 3(x-5)+10=5x | | x+5(x+6)+25-12(x-12+5)=25 | | 0.5x+3=x^2 | | x/3+2=8 | | 2(x+4)/5=3x-1 |

Equations solver categories